(untitled) - Jarez, Jon (New York, 2011)
This title's 'Learn by Doing' theme is incorporated in each lesson so students can experience hands-on learning throughout the entire text. Students first focus on the introductory skills that are isolated in each lesson and then complete individual skill exercises that ensure a clear learning path.
Keywords: Microsoft Access,Database management,Quản lý dữ liệu,Phần mềm Access